Indonesia Dalam Menghadapi Liberalisasi Bidang Jasa Pada Tahun 2010 - Nurhidayat, R (Badan kebijakan Fiskal, 2010)
This is a paper aiming to capture Indonesia's position with regard implementation of Vientiane Action Programme (VAP) mainly in services sector. According to the programe, there are four services sector that will be applied in 2010 which are air travel, information and comunication technology, healthcare, and tourism. A description analysis is used to describe the services sector in both ASEAN and domestic scope.The findings suggest that tourism is one of the sectors which need more atention. Compared with the others, This sector has the bigest share of GDP and national employment. Finally, services liberalization should be applied gardually to minimised negative impact of liberalization